2020
DOI: 10.1093/ckj/sfaa271
|View full text |Cite
|
Sign up to set email alerts
|

The ERA-EDTA Registry Annual Report 2018: a summary

Abstract: Background The European Renal Association – European Dialysis and Transplant Association (ERA-EDTA) Registry collects data on kidney replacement therapy (KRT) via national and regional renal registries in Europe and countries bordering the Mediterranean Sea. This article summarizes the 2018 ERA-EDTA Registry Annual Report, and describes the epidemiology of KRT for kidney failure in 34 countries. Methods Individual patient dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 1 publication
2
62
1
6
Order By: Relevance
“…In this study, 1st-year mortality of the patients who underwent LKDT in our center was 1.67%. TSN 2019 registry reports revealed that 1st-year mortality 2.85% (9), US 2019 registry reports revealed that 1st-year mortality 2% (10), European Renal Association-European Dialysis, and Transplant Association (ERA-EDTA) 2017 reports showed that 1st-year mortality 1.2% (11), which was also very similar to our results. This study showed that recipient age, dialysis treatment and HLA mismatch numbers are independent risk factors for 1st-year mortality after LDKT.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, 1st-year mortality of the patients who underwent LKDT in our center was 1.67%. TSN 2019 registry reports revealed that 1st-year mortality 2.85% (9), US 2019 registry reports revealed that 1st-year mortality 2% (10), European Renal Association-European Dialysis, and Transplant Association (ERA-EDTA) 2017 reports showed that 1st-year mortality 1.2% (11), which was also very similar to our results. This study showed that recipient age, dialysis treatment and HLA mismatch numbers are independent risk factors for 1st-year mortality after LDKT.…”
Section: Discussionsupporting
confidence: 90%
“…End-stage renal disease (ESRS) is a health issue that extends worldwide as it requires long term care and in the same time, is very costly. Prevalence of chronic renal failure increases in various countries (1) .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the survival of patients receiving organ transplantation remains unsatisfactory, with a five-year survival of 89.6% ( 75 ), 86.6% ( 76 ), and 77% ( 77 ) in the liver, kidney, and heart transplantation, respectively. Although immunosuppression has been widely used to inhibit acute graft- vs -host disease after organ transplantation ( 78 ), many complications (like heart failure or acute kidney injury) increase morbidity and mortality ( 79 ).…”
Section: Discussionmentioning
confidence: 99%